Modelling rheumatic heart disease progression in australia using disease register data linked to administrative records. (11th May 2021) - Stacey, I; Hung, J; Murray, K; Seth, R; Bond-Smith, D; Katzenellenbogen, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Australian Government National Health and Medical Research Council OnBehalf: ERASE project Background: Rheumatic Heart Disease (RHD) is a major contributor to morbidity and mortality globally, and is endemic among Indigenous Australians. The RHD Endgame strategy was recently launched, outlining comprehensive methods for eliminating RHD in Australia by 2031. However, there is currently limited information on national rates of RHD and progression to severe or complicated RHD. Purpose: This study provides current estimates of RHD progression prior to RHD Endgame Strategy implementation. We estimate the probability and predictors of progressing from RHD diagnosis to cardiovascular complications, death, or need for surgical intervention in the Australian population from expanded data sources, addressing methodological shortcomings in existing evidence by using cross-jurisdictional administrative datasets and a competing risks approach. Methods: This retrospective cohort study used linked RHD register, hospital and death data from five Australian jurisdictions (>70% Australians). Progression from RHD diagnosis to all-cause mortality, non-fatal cardiovascular complications (heart failure, stroke, endocarditis, atrial fibrillation), or need for surgical intervention were estimated for people aged <35years diagnosed with first-ever RHD between 2010 and 2018. A minimum 8.5-year look-back excluded prevalent cases; maximum follow-up was 8 years. Proportional cause-specific hazard regression modelling investigated independent predictors of outcomes, with death treated as a competing risk.  Sensitivity analyses compared results between all-sources and register-only cohorts. Results: We identified 1714 first-ever RHD cases aged <35years in the all-sources cohort (84% Indigenous, 11% migrant, 63% women, 40% age 5-14years, 85% non-metropolitan). Six months after diagnosis, 8.1% (95%CI:6.9-9.5%) had experienced heart failure, other cardiovascular complications or surgical intervention and 23.6% (95%CI:20.2-27.5%) progressed to these outcomes within 8 years. The register-only cohort experienced less disease progression with estimated composite event rates of 5.6% (95%CI:4.7-6.6%) and 18.4% (95%CI:16.6-20.5%) at 6 month and 8 years respectively. Death rate in the all-sources cohort was 0.5% at 6 months and 3.2% at 8 years. Older age, Metropolitan residence, and history of acute rheumatic fever, but not sex or Indigenous status, were independent predictors of major cardiovascular outcomes. Conclusions: This study provides the most definitive and contemporary estimates of RHD disease progression in young Australians. Despite Australia"s excellent healthcare system infrastructure, RHD complication rates remain high.  Improvements in healthcare systems for diagnosis, monitoring, and management of RHD cases will need to be implemented in both Metropolitan and remote settings as Australia implements its Endgame strategy against RHD. However, primordial and primary prevention provides the best potential to reduce the burden of RHD in Australia and beyond.